2011
DOI: 10.1021/ic102579t
|View full text |Cite
|
Sign up to set email alerts
|

Gd(III)[15-Metallacrown-5] Recognition of Chiral α-Amino Acid Analogues

Abstract: Chiral Ln(III)[15-metallacrown-5] complexes with phenyl side chains have been shown to encapsulate aromatic carboxylates reversibly in their hydrophobic cavities. Given the importance of selective guest binding for applications of supramolecular containers in synthesis, separations, and materials design, the affinity of Gd(III)[15-metallacrown(Cu(II), L-pheHA)-5] hosts for a series of chiral carboxylate guests with varying substitutions on the α-carbon (phenylalanine, N-acetyl-phenylalanine, phenyllactate, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 81 publications
0
32
1
Order By: Relevance
“…This is why the U.S. Food and Drug Administration (FDA) has laid down strict guidelines on the identification and quantification of chiral compounds [186][187][188][189]. Therefore, enantioselectivity is one of the most important goals for the sensing of organic substances [190][191][192][193][194][195][196][197][198], because biological activity is strictly correlated with stereochemistry. Although some enantioselective methods based on capillary electrophoresis [199][200], voltammetry [201], colorimetric methods [202][203][204] etc.…”
Section: Chiral/enantiomeric Recognitionmentioning
confidence: 99%
“…This is why the U.S. Food and Drug Administration (FDA) has laid down strict guidelines on the identification and quantification of chiral compounds [186][187][188][189]. Therefore, enantioselectivity is one of the most important goals for the sensing of organic substances [190][191][192][193][194][195][196][197][198], because biological activity is strictly correlated with stereochemistry. Although some enantioselective methods based on capillary electrophoresis [199][200], voltammetry [201], colorimetric methods [202][203][204] etc.…”
Section: Chiral/enantiomeric Recognitionmentioning
confidence: 99%
“…Chirality is a prominent characteristic of biological molecules, and enantiomers of a chiral molecule often exhibit striking differences in terms of their physiological responses . Therefore, enantiomers have been widely applied to the various fields of science and technology, such as catalytic chemistry, biotechnology, and especially pharmaceutical science . Consequently, numerous efforts have been devoted to the synthesis and application of artificial chiral host and/or receptors .…”
Section: Introductionmentioning
confidence: 99%
“…[3] A large amount of systematic structural studies of Ln[15MC CuRha -5] complexes derived from α-aminohydroxamic acids with various organic anions have been performed, [4][5][6][7][8][9][10][11][12][13][14] and the affinity of the Ln III ion Scheme 1. It has been demonstrated that the anion affinity for the metallacrown is dependent on the R-substituted hydroximate ligands (Rha).…”
Section: Introductionmentioning
confidence: 99%